Electrical degradation and breakdown in polymers - Dissado, L. A. (Len A.); Fothergill, J. C. (John C.) (Institution of Engineering and Technology, 1992)
The book has 19 chapters and is divided into 5 parts.The first part deals with polymer structure and morphology. The second part covers electrical treeing degradation, water treeing degradation and factors affecting treeing. The third part deals with charge injection and transport. The fourth part covers statistical features of electrical breakdown. The fifth part covers the engineering aspects of breakdown testing.